A legal analysis of prohibition of marine pollution - Bapela, Mpho Paulos (My University, 2016)
This mini-dissertation deals with the legal analysis of the prohibition of marine pollution. It is found that the harmful effects of marine pollution on the marine ecosystem, human health and the economy is a problem that needs to be solved immediately. International Conventions and different legislation have been drafted in order to regulate, reduce, mitigate or stop marine pollution. Despite the existence of these conventions and legislation, this problem continues unabated. Large numbers of marine species are known to be harmed and killed as a result of marine pollution. Marine pollution did not receive much attention until many species in the sea and the marine ecosystem faced adverse consequences resulting from marine pollution. Although it has become a global concern, most nations are still producing huge pollution loads. This mini-dissertation analyses the legal framework and the sources of marine pollution, the effects of marine pollution on the marine ecosystem and human health. Furthermore, it makes a comparative analysis between South Africa as developing country and Australia as a developed country in order to determine what South Africa could learn from Australia. The study makes recommendations on how marine pollution can be solved, mitigated or combatted.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Marine pollution; Ecosystem; Human health; Marine pollution -- Law and legislation; Marine ecosystem health; Marine resources conservation